Pengaruh tax avoidance, tax reporting aggressiveness, dan tax risk terhadap risiko perusahaan - Gita Warastri, Reyka Martina; Suryaningrum, Diah Hari (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to analyze the effect of tax avoidance, tax reporting aggressiveness, tax risk on corporate risk as proxied by the volatility of stock returns with institutional ownership as moderating. Manufacturing companies become the population with a sample selection technique, namely purposive sampling. Samples obtained is 34 with the 2016-2020 research period, which means the total number of data is 170. The type of data is secondary data that can be accessed through the Indonesia Stock Exchange and Yahoo Finance. Multiple regression analysis and moderating regression analysis were used in the data analysis technique using SPSS version 25. This study found that tax risk had an effect on corporate risk, while tax avoidance and tax reporting aggressiveness had no effect on corporate risk. Then the institutional ownership cannot moderate the effect of tax avoidance, aggressiveness of tax reporting, and tax risk on company risk.